2015
DOI: 10.1186/s12929-014-0109-8
|View full text |Cite
|
Sign up to set email alerts
|

Molecular regulation of the expression of leptin by hypoxia in human coronary artery smooth muscle cells

Abstract: BackgroundLeptin, produced mainly by white adipose tissue, is a hormone that promotes vascular smooth muscle cell (VSMC) migration and proliferation, a process involved in the pathophysiology of atherosclerosis. Leptin expression in human coronary artery smooth cell (HCASMC) is induced by hypoxia. However, our understanding of the process of atherosclerosis in HCASMC is only emerging. Since the mechanisms by which hypoxia regulates leptin in HCASMC are as yet unknown, this study aims to investigate the mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…However, the specific mechanism underlying NAC involvement in the HG-induced injury in vascular endothelial cells is still not clear. Previous studies found that NAC could reduce the expression level of leptin to some extent [26] and inhibit angiogenesis by inhibiting the expression of leptin [9] . Therefore, it was speculated that NAC might be able to antagonize HG-induced multiple injuries in vascular endothelial cells through inhibiting the expression of leptin/LEPR, which was also confirmed in this study.…”
Section: Discussionmentioning
confidence: 96%
“…However, the specific mechanism underlying NAC involvement in the HG-induced injury in vascular endothelial cells is still not clear. Previous studies found that NAC could reduce the expression level of leptin to some extent [26] and inhibit angiogenesis by inhibiting the expression of leptin [9] . Therefore, it was speculated that NAC might be able to antagonize HG-induced multiple injuries in vascular endothelial cells through inhibiting the expression of leptin/LEPR, which was also confirmed in this study.…”
Section: Discussionmentioning
confidence: 96%
“…However, the specific mechanism underlying NAC involvement in the HG-induced injury in vascular endothelial cells is still not clear. Previous studies found that NAC could reduce the expression level of leptin to some extent [28] and inhibit angiogenesis by inhibiting the expression of leptin [9] . Therefore, it was speculated that NAC might be able to antagonize HG-induced multiple injuries in vascular endothelial cells through inhibiting the expression of leptin/LEPR, which was also confirmed in this study.…”
Section: Discussionmentioning
confidence: 96%
“…HIF-1α is a protein that regulates hypoxia-regulated gene expression to mediate cell adaption to low oxygen circumstances [ 60 , 61 ]. ISO injections in rats have been shown to increase HIF-1α expression [ 62 ].…”
Section: Discussionmentioning
confidence: 99%